Calculating a natural world : scientists, engineers, and computers during the rise of U.S. cold war research - Akera, Atsushi (Inside technology., 2007)
How the complex interplay of academic, commercial, and military interests produced an intense period of scientific discovery and technological innovation in computing during the Cold War.